2000
DOI: 10.1021/bp000090b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ammonia on the Glycosylation of Human Recombinant Erythropoietin in Culture

Abstract: Recombinant human erythropoietin (EPO) was produced by a stable transfected CHO-K1 cell clone (EPO-81) grown in serum-free medium. Our previous work showed that there was a significant increase in the heterogeneity of the glycoforms of EPO and a reduction of the sialylation at 20 mM NH(4)Cl. In the work presented here, the effects of ammonia on EPO N-linked oligosaccharides were analyzed. EPO was purified from culture supernatants by immunoaffinity chromatography. The N-linked oligosaccharides were released en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 41 publications
3
46
0
1
Order By: Relevance
“…Six discrete bands were identi®ed with a molecular size range of 33± 39 kD and pI values from 4.1 to 4.4. These are the expected ranges of glycosylated EPO with variable terminal sialylation of the N-glycan structures (Yang and Butler, 2000b). Identical patterns were obtained with EPO samples taken from T-¯asks and the stirred-tank bioreactor.…”
Section: The Glycosylation Of Eposupporting
confidence: 58%
“…Six discrete bands were identi®ed with a molecular size range of 33± 39 kD and pI values from 4.1 to 4.4. These are the expected ranges of glycosylated EPO with variable terminal sialylation of the N-glycan structures (Yang and Butler, 2000b). Identical patterns were obtained with EPO samples taken from T-¯asks and the stirred-tank bioreactor.…”
Section: The Glycosylation Of Eposupporting
confidence: 58%
“…For example, Ozturk and Palsson [81] showed that the actual uptake of glutamine in hybridoma cell culture was three-fold lower than the apparent uptake.Ammonium that is released via glutaminolysis and glutamine decomposition is a toxic by-product in mammalian cell cultures [84]. Ammonium can accumulate to levels up to 2-10 mM in batch cultures [11], and can negatively affect cell growth [85][86][87][88], protein production [89] and protein glycosylation [9,[90][91][92][93]. Schneider et al [8] suggested that alanine aminotransferase and aspartate aminotransferase reactions act as a detoxification process for ammonium removal.…”
Section: Glutaminolysis and Tca Cyclementioning
confidence: 99%
“…3 Other factors such as the level of glucose, glucoseamine, ammonia, dissolved oxygen, temperature and the time of culture have all affected the glycosyaltion of either specific protein analyzed or the overall protein glycosylation. [4][5][6][7][8][9][10] Significantly, these changes were attributed to alternations in intracellular glycosyaltion rather than degradation of carbohydrate side chains after secretion of the protein to the media. [4][5][6]9 Mechanistically, these changes can be translated to changes in intracellular compartments that are responsible for glycosylation.…”
Section: Immune Recognition Is Often Based On Recognition Of Carbohydmentioning
confidence: 99%